2008
DOI: 10.1007/s11255-008-9467-z
|View full text |Cite
|
Sign up to set email alerts
|

Adverse prognostic impact of capsular incision at radical prostatectomy for Japanese men with clinically localized prostate cancer

Abstract: Despite the lack of independent significance, the presence of CI has an adverse impact on biochemical outcome in patients undergoing RP for clinically localized prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Only 30 PSMs were present in our study and therefore reduced the statistical power of our analysis. However, our PSM rate was comparable with other studies of a similar nature, for example Kumano et al (2009) [29], suggesting that the population was representative. Another limitation of the current study was that data were missing for many of the patients in our database.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Only 30 PSMs were present in our study and therefore reduced the statistical power of our analysis. However, our PSM rate was comparable with other studies of a similar nature, for example Kumano et al (2009) [29], suggesting that the population was representative. Another limitation of the current study was that data were missing for many of the patients in our database.…”
Section: Discussionsupporting
confidence: 91%
“…For example, several studies have found incidence of IPI to be 1.8–2.8 % [9, 11, 28]. However, some studies have reported rates of IPI as high as 20 % [29]. Indeed, in our study, 30 patients (16.4 %) presented with PSMs in T2 disease (IPI).…”
Section: Discussionmentioning
confidence: 48%
“…In our previous reports, isolated IPI rates in OC disease ranged from 1.8% to 2.3% [8,16]. However, others reported the IPI rates in OC disease as high as 20% [9,15]. This variation in IPI rate can be partly attributed to pathologic interpretation.…”
Section: Discussionmentioning
confidence: 90%
“…Most studies that evaluated the prognostic significance of IPI reported the IPI rate in men with organ-confined (OC) disease only [69,15]. The current study was performed to evaluate the IPI rate across different pathologic stages and to identify predictors of IPI.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely explained by the fact that we used a strict definition of PNI, that of circumferential encirclement of nerves by malignant glands. In contrast, prior studies reporting a higher PNI prevalence either did not describe how PNI was defined (14, 19, 20, 25, 39) or used vague descriptions such as presence of tumor cells “in the perineural space” (16, 18) or “along the perineural sheath” (21). Because the perineural space can often be difficult to identify using H&E stains alone, abutment of the perineural space by both malignant and benign glands can, in the absence of circumferential involvement, be misinterpreted as PNI (53, 54), resulting in misclassification.…”
Section: Discussionmentioning
confidence: 98%